Availability of caregiver-friendly workplace policies (CFWPs): an updated international scoping review protocol - Allison Williams; Reed Ciarloni (BMJ Publishing Group, 2024)
Background This scoping review will provide an update on the availability of caregiver-friendly workplace policies (CFWPs) internationally. As the global population continues to age, there is a growing demand for unpaid care. Many individuals providing unpaid care remain in the workforce, increasing the number of carer-employees (CEs). The goal of this review is to determine how workplaces are supporting the growing number of CEs via CFWPs compared with 5 years ago, while identifying and prioritising actions that will improve workplace support for CEs. It is expected that this scoping review will provide: valuable insights on how broader social and cultural issues shape CFWPs; identification of leading workplaces that provide CFWPs, as well as; labour sectors that require improvement. Comparative analysis between the previous published scoping reviews will allow for further conclusions with respect to the changing landscape of CFWPs over time.Methods This scoping review will be conducted with methodological guidance from the Joanna Briggs Institute (JBI) Reviewers Manual, the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for scoping reviews guidelines and checklist and the scoping review protocol checklist by JBI. As recommended by the JBI, this scoping review uses the Population/Context/Concept framework to identify main concepts and appropriate inclusionary/exclusionary criteria. This review will include literature (peer-reviewed and grey) published between 1 May 2019 and 31 May 2023, in the English language, that discuss the provision of unpaid care to older adults; workplaces deemed caregiver and/or family friendly related to CFWPs and explicit identification of the workplace/organisation by name. Results will be communicated via tables, diagrams and content analysis.Ethics approval and dissemination Ethics approval for this study is not applicable. The results of this study will be disseminated through peer-reviewed publication and conferences.